Identification of protein interactions of grapevine fanleaf virus RNA-dependent RNA polymerase during infection of Nicotiana benthamiana by affinity purification and tandem mass spectrometry. (27th May 2021) - Osterbaan, Larissa J.; Hoyle, Victoria; Curtis, Michelle; DeBlasio, Stacy; Rivera, Keith D.; Heck, Michelle; Fuchs, Marc
Abstract : The RNA-dependent RNA polymerase (1E Pol ) is involved in replication of grapevine fanleaf virus (GFLV, Nepovirus, Secoviridae ) and causes vein clearing symptoms in Nicotiana benthamiana . Information on protein 1E Pol interaction with other viral and host proteins is scarce. To study protein 1E Pol biology, three GFLV infectious clones, i.e. GHu (a symptomatic wild-type strain), GHu-1EK802G (an asymptomatic GHu mutant) and F13 (an asymptomatic wild-type strain), were engineered with protein 1E Pol fused to a V5 epitope tag at the C-terminus. Following Agrobacterium tumefaciens -mediated delivery of GFLV clones in N. benthamiana and protein extraction at seven dpi, when optimal 1E Pol :V5 accumulation was detected, two viral and six plant putative interaction partners of V5-tagged protein 1E Pol were identified for the three GFLV clones by affinity purification and tandem mass spectrometry. This study provides insights into the protein interactome of 1E Pol during GFLV systemic infection in N. benthamiana and lays the foundation for validation work.